Enhancement of effectiveness of invention activities of Vietnam public universities through recovering barriers of these activities - Hai Yen, Hoang Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
One of the indicators to evaluate competitiveness of universities is their scientific research capacities where inventions are specific products of research activities. The quantity and quality of inventions present not only research capacities of universities but also science-technology (S&T) and economic competitiveness of a nation. Universities could not keep outside positions in activities of invention creation and protection in the mission for national S&T and economic development. However, the quantity and quality of inventions developed by Vietnamese universities remain limited. This paper shows the actual situation of activities of inventions in Vietnam public universities. Some notions related to inventions and invention protection are referred Vietnam’s Intellectual Property Law, 2005 which was revised and amended in 2009. Invention activities in public universities are referred to a series of activities to create and explore inventions as well as to protect them from their funding sources. It is necessary to note the main tasks of universities are training and researching. Therefore, the center of evaluation of the effectiveness of invention activities of universities is not mainly turned to economic-commercial aspects. Code: 13062701